1999
DOI: 10.1159/000007585
|View full text |Cite
|
Sign up to set email alerts
|

Water Extracts of <i>Helicobacter pylori</i> Delay Healing of Chronic Gastric Ulcers in Rats: Role of Cytokines and Gastrin-Somatostatin Link

Abstract: Background: Helicobacter pylori (Hp) is considered as a major risk factor of peptic ulcer, but the pathogenic mechanism of its action has not been fully explained. Aims: This study was designed: (1) to compare the ulcer healing effects of water extract (WE) obtained from type-I cytotoxin-associated gene A (CagA) and vacuolating cytotoxin A (VacA) expressing Hp and from type-II CagA- and VacA-negative Hp strain with those of vehicle (saline), and (2) to determine the alterations in gastric secretion, gastric bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Moreover, HP LPS exhibits a reduced endotoxic potency in terms of pyrogenicity, lethality, toxicity, mitogenicity and cytokine release [4, 29]. In general, bacterial-derived LPS induce the expression of COX-2 as well as of proinflammatory cytokines, which by themselves are potent inducers of COX-2 expression [6, 7, 8, 30, 31, 32]. Additionally, it has been demonstrated that bacterial endotoxin stimulates the generation of iNOS, with subsequent release of NO and activation of COX-2 [10, 12, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HP LPS exhibits a reduced endotoxic potency in terms of pyrogenicity, lethality, toxicity, mitogenicity and cytokine release [4, 29]. In general, bacterial-derived LPS induce the expression of COX-2 as well as of proinflammatory cytokines, which by themselves are potent inducers of COX-2 expression [6, 7, 8, 30, 31, 32]. Additionally, it has been demonstrated that bacterial endotoxin stimulates the generation of iNOS, with subsequent release of NO and activation of COX-2 [10, 12, 30].…”
Section: Discussionmentioning
confidence: 99%
“…A similar depletion of luminal SST release has been demonstrated in male Wistar rats treated with water extract obtained from type I H. pylori. 43 Cats with acquired natural H. pylori infection (cag A Ϫ , pic B Ϫ ) demonstrated fasting plasma gastrin concentrations and pentagastrin-simulated acid secretion levels that were similar to those in uninfected cats. The amount of SST and the number of immunoreactive SST cells in antral tissue were lower in uninfected than in H. pylori-infected cats, 44 in contrast to other reports.…”
Section: Animal Studies Of the Effect Of H Pylori Infection On Peptidesmentioning
confidence: 91%
“…The fact that antibiotics and acid pump inhibitors prevented delayed healing resulting from H. pylori have offered valuable insights into the mechanisms of ulcer healing. Konturek's group 68,69) reported that Cag A and Vac A positive H. pylori water extract could delay ulcer healing in mice and rats. They contend that the underlying mechanism involves reduction of gastric mucosal blood flow, over-expression of cytokines, such as IL-1b and TNFa, and disruption of the balance between serum gastrin/somatostatin.…”
Section: Cox-2 and Paf Inhibitors And Plateletsmentioning
confidence: 99%